Branding Strategy in Improving Madrasah Competitiveness - Istiqomah, Nurul; Oktavianti, Mutia; Subiyantoro, Subiyantoro (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2025)
Competition among primary educational institutions in the modern era is increasingly competitive, especially for private schools which are required to attract public trust through a superior image. In this context, branding is a crucial strategy for strengthening an institution's identity and competitiveness. This research aims to describe the branding strategy implemented by MI Islamiyah Muhammadiyah Sumberberas to enhance the competitiveness of a primary educational institution in Banyuwangi regency. The research approach used is descriptive qualitative, with data collected through interviews, observation, and documentation. The results show that MI Islamiyah Muhammadiyah Sumberberas has successfully built an integrated brand through the establishment of a clear vision and mission, optimal service, utilization of communication media, provision of adequate facilities and infrastructure, development of flagship and extracurricular programs, targeted promotion, appreciation for high-achieving students, and collaboration with various parties. The implemented branding strategy not only impacts the enhancement of public image and trust but also strengthens the loyalty of students, teachers, and parents towards the institution. The findings of this research affirm the importance of professional and adaptive brand management as the primary key to building a competitive advantage for private educational institutions. This research also provides theoretical and practical contributions for educational institution managers in designing relevant, effective, and sustainable branding strategies.